Experimental and Numerical Study of the Flexural Performance of Spontaneous Combustion Gangue Coarse Aggregate Concrete Laminated Slab - Kai Zhang; Mei Zhou; Boqun Zhang; Congqi Luan; Chao Li; Yan Liu; Yue Gao; Yanfu Yu (Buildings, 2023)
(1) Background: to study the differences in flexural performance and failure characteristics of spontaneous combustion gangue coarse aggregate concrete (SCGAC) laminated slabs and ordinary concrete laminated slabs, comparative flexural performance tests of one ordinary concrete laminated slab and four spontaneous combustion gangue coarse aggregate concrete laminated slabs (SCGACLSs) full-scale specimens were carried out. (2) Methods: The loading method was four-point unidirectional static loading; the failure mode, load–deflection curve, load–reinforcement strain curve, and load–concrete strain curve of each specimen were analyzed. In addition, the load–deflection curve of the five slabs were predicted by ABAQUS. (3) Results: The five laminated slabs showed similar behaviors in terms of failure mode, load–strain curve, load–deflection curve, and deformation and all the properties satisfied the Chinese standard GB50010 (2010). Compared with ordinary concrete laminated slabs, the cracking load of SCGACLS with a precast layer of SCGAC(C30) decreased by 15.2% and the span deflection increased by 28.3% in the ultimate condition; however, when the strength grade of SCGAC of the precast layer was increased to SCGAC(C40), the cracking load increased by 7.8% and the span deflection was similar to that of the ordinary concrete laminated slabs. All specimens conformed to the planar section assumption. In addition, the finite element model (FEM) prediction results showed that the maximum relative errors of load and deflection were <5% and <10%, respectively, indicating that the established FEM had high prediction accuracy. (4) Conclusions: The defects of reduced load-carrying capacity and uncoordinated deformation caused by the different elastic modulus of precast and cast-in-place layer concrete can be compensated by appropriately increasing the strength grade of precast layer concrete of SCGACLSs. The application of SCGACLSs in structures is feasible.